Unraveling Genetic Relationship and Morphological Divergence of Rasbora tornieri (Ahl, 1922) across Sumatra Island: Genetic and Morphological Study of Rasbora tornieri - Prawira, Furqan; Syaifullah; Tjong, Djong; Aadrean; Maideliza, Tesri; Roesma, Dewi (Journal of Tropical Life Science, 2025)
Previous research indicates that the genetic diversity of Rasbora tornieri (Ahl, 1922) from the Musi River population in South Sumatra is notably low compared to populations from Borneo. Historical river connections between Sumatra and Borneo likely influence this low genetic diversity. However, the distribution of Rasbora tornieri across multiple geographic locations in Sumatra may contribute to significant genetic and morphological variations within this species. This study aims to elucidate the phylogenetic relationships and morphological variation of Rasbora tornieri across its known distribution in Sumatra. A comprehensive approach integrating molecular and morphological analyses was employed. Mitochondrial genes, Cytochrome c Oxidase subunit 1 (COI, 655 bp) and Cytochrome B (Cyt B, 629 bp), were sequenced, and morphological assessments were conducted. Phylogenetic and genetic diversity analyses revealed high genetic differentiation among populations. Morphological variations were statistically supported by the Mann-Whitney test, Principal Component Analysis (PCA), and Unweighted Pair Group Method with Arithmetic Mean (UPGMA) clustering, further highlighting population divergence. These findings indicate that geographic isolation and environmental factors influence the genetic and morphological diversity of Rasbora tornieri. Understanding these variations is crucial for conservation efforts, particularly amid habitat degradation and overfishing. This study provides valuable insights into freshwater fish biodiversity in Southeast Asia